Двоточкова задача для еволюційних рівнянь з псевдобесселевими операторами - Городецький, В.В.; Мироник, В.І. (Видавничий дім "Академперіодика" НАН України, 2008)
The correct solubility of a two-point problem for the evolution equation with pseudo-Bessel operators of infinite order in the class of boundary conditions which are generalized functions of the distribution type is established.